Application of Directional Long Borehole Technology in Working Face of Thick Coal Seam Along Top Driving. Issue 4 (April 2020) - Shi, Yongtao
Abstract: With the increasing of gas content in a coal mine in Shanxi Province, when the coal seam roadway is driving along the top, the extraction effect of ordinary borehole is not good under the complicated geological condition of high gas content and thick coal seam. The traditional "step type" gas control method of ordinary borehole has seriously affected the mine excavation replacement and safety production. In view of the existing problems of gas control in mine heading face, this paper introduces the technology of long directional borehole extraction. Through the field test, investigation, comparison and analysis, the tunneling speed of the tunnel is increased from the original 150m / month to 240m / month; compared with the safe excavation of the 400m roadway, the directional long borehole extraction process was 37 days faster than the traditional ordinary borehole extraction process; the gas concentration in the working face and return air flow was reduced by about 0.3% on average, which greatly reduced the ventilation pressure during the excavation and ensured the safe excavation of the working face. Finally, the extraction technology and parameters of the long directional borehole along the heading face of the thick coal seam are investigated.